2012
DOI: 10.1016/j.ultramic.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

EEL spectroscopic tomography: Towards a new dimension in nanomaterials analysis

Abstract: Electron tomography is a widely spread technique for recovering the three dimensional (3D) shape of nanostructured materials. Using a spectroscopic signal to achieve a reconstruction adds a fourth chemical dimension to the 3D structure. Up to date, energy filtering of the images in the transmission electron microscope (EFTEM) is the usual spectroscopic method even if most of the information in the spectrum is lost. Unlike EFTEM tomography, the use of electron energy-loss spectroscopy (EELS) spectrum images (SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…By acquiring EELS spectrum images (SI) in a TEM at different tilt angles (i.e., tomography), it is possible to obtain a 3D reconstruction of the elemental distribution in the material. For instance, EELS-SI tomography has been used to chemically determine the 3D structure of Co 3 O 4 /Fe x Co (3-x) O 4 core/shell mesoporous particles down to pore resolution [217].…”
Section: Rising Techniquesmentioning
confidence: 99%
“…By acquiring EELS spectrum images (SI) in a TEM at different tilt angles (i.e., tomography), it is possible to obtain a 3D reconstruction of the elemental distribution in the material. For instance, EELS-SI tomography has been used to chemically determine the 3D structure of Co 3 O 4 /Fe x Co (3-x) O 4 core/shell mesoporous particles down to pore resolution [217].…”
Section: Rising Techniquesmentioning
confidence: 99%
“…Whilst X-rays and EFTEM mainly allow the mapping of elemental contents, EELS offers additional possibilities for studying detailed chemistry. Early studies have already shown the feasibility of EELS-STEM tomography [2,3]. Nevertheless, EELS suffers significantly from multiple scattering, especially for thicker specimens, and this makes the backgroundsubtracted edge signal a non-linear function of thickness, which leads to reconstruction artifacts.…”
Section: Linear Chemically Sensitive Electron Tomography Using Dualeementioning
confidence: 99%
“…This problem can be overcome by using spectroscopic techniques such as energy dispersive X-ray imaging (EDX) or electron energy loss spectroscopy (EELS). In the past, electron tomography in combination with EELS imaging techniques was applied to investigate nanostructures in both materials science and biology [3][4][5][6][7][8]. In most studies, 2D elemental maps of the object are first calculated at each tilt angle and used as an input for tomographic reconstruction.…”
Section: Introductionmentioning
confidence: 99%